THE ROLE OF AN ENGLISH TEACHER IN THE DEVELOPMENT OF CREATIVE THINKING AND CREATIVE ABILITIES OF STUDENTS (Innovative Technologica: Methodical Research Journal, 2023)
Modern requirements for the educational process have increased, modern realities dictate new approaches to the educational process. In this article highlights of the role of an English teacher in the development of creative thinking and creative abilities of students.